2017
DOI: 10.1038/s41598-017-04007-x
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin Sulfate Is Required for Onset and Offset of Critical Period Plasticity in Visual Cortex

Abstract: Ocular dominance plasticity is easily observed during the critical period in early postnatal life. Chondroitin sulfate (CS) is the most abundant component in extracellular structures called perineuronal nets (PNNs), which surround parvalbumin-expressing interneurons (PV-cells). CS accumulates in PNNs at the critical period, but its function in earlier life is unclear. Here, we show that initiation of ocular dominance plasticity was impaired with reduced CS, using mice lacking a key CS-synthesizing enzyme, CSGa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 74 publications
2
70
0
Order By: Relevance
“…In early postnatal cortical development, expression of PNNs increases progressively with the maturation of that network. An excellent example is the primary visual cortex where the developmental increase of PNNs is regulated by visual experience (Beurdeley et al, 2012;Hou et al, 2017). PNNs in mature primary visual cortex mainly surround the soma and proximal dendrites of PV+ interneurons (Celio, 1993;Hartig et al, 1992;Ueno et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In early postnatal cortical development, expression of PNNs increases progressively with the maturation of that network. An excellent example is the primary visual cortex where the developmental increase of PNNs is regulated by visual experience (Beurdeley et al, 2012;Hou et al, 2017). PNNs in mature primary visual cortex mainly surround the soma and proximal dendrites of PV+ interneurons (Celio, 1993;Hartig et al, 1992;Ueno et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Perineuronal nets (PNNs) are specialized extracellular matrix structures that can act as physical barriers or modulators of plasticity, restrict axon regeneration, and form molecular brakes that actively control synaptic maturation and the function of cortical parvalbumin+ (PV+) GABAergic interneurons that drive gamma oscillations (Bartos et al, 2002;Begum and Sng, 2017;Bernard and Prochiantz, 2016;Carstens et al, 2016;Deepa et al, 2002;Dityatev et al, 2007;Donato et al, 2013;Durand et al, 2012;Frischknecht et al, 2009;Gundelfinger et al, 2010;Hartig et al, 1992;Hou et al, 2017;Kalemaki et al, 2018;Kosaka and Heizmann, 1989;Krishnan et al, 2015Krishnan et al, , 2017Nakagawa et al, 1986;Orlando et al, 2012;Pizzorusso et al, 2002Pizzorusso et al, , 2006Sigal et al, 2019;Sugiyama et al, 2009;Suttkus et al, 2012;Ueno et al, 2018;Vo et al, 2013;de Winter et al, 2016;Ye and Miao, 2013). Mature PNNs in the adult cortices are thought to be stable structures, inhibitory to plasticity, and perhaps play roles in long term memory such as "engrams" (Carstens et al, 2016;Gogolla et al, 2009;Thompson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Once Otx2 is enriched around PV cells via the interaction with PNN, it seems to penetrate the cells through a positively charged internalization sequence (Prochiantz & Joliot, ; Sugiyama et al., ). In contrast to the prevailing notion that PNN inhibits the plasticity as a physical barrier, a new study using mice lacking a key CS‐synthesizing enzyme, chondroitin sulfate N ‐acetylgalactosaminyltransferase 1 (CSGalNAcT1), showed that a small amount of PNN is essential to open the critical period by promoting accumulation of Otx2 in PV cells (Hou et al., ; Igarashi, Takeuchi, & Sugiyama, ). As CSGalNAcT1 is a target gene of Otx2 (Sakai et al., ), continuous internalization of Otx2 then accelerates further PNN formation, which in turn consolidates PV cell function and closes the critical period.…”
Section: Otx2 Homeoprotein Is a Messenger Of Experience To Regulate Tmentioning
confidence: 99%
“…How is Otx2 targeted to PV cells? Recent studies showed that Otx2 binds to chondroitin sulfate proteoglycan (CSPG) in PNN via its glycosaminoglycan‐binding motif (Beurdeley et al., ; Miyata, Komatsu, Yoshimura, Taya, & Kitagawa, ) and also interacts with a major CSPG, aggrecan (Hou et al., ). Once Otx2 is enriched around PV cells via the interaction with PNN, it seems to penetrate the cells through a positively charged internalization sequence (Prochiantz & Joliot, ; Sugiyama et al., ).…”
Section: Otx2 Homeoprotein Is a Messenger Of Experience To Regulate Tmentioning
confidence: 99%
See 1 more Smart Citation